EEG indices of reward motivation and target detectability in a rapid visual detection task. - Hughes, G; Mathan, S; Yeung, N (2013)
A large corpus of data has demonstrated the sensitivity of behavioral and neural measures to variation in the availability of reward. The present study aimed to extend this work by exploring reward motivation in an RSVP task using complex satellite imagery. We found that reward motivation significantly influenced neural activity both in the preparatory period and in response to target images. Pre-stimulus alpha activity and, to a lesser degree, P3 and CNV amplitude were found to be significantly predictive of reward condition on single trials. Target-locked P3 amplitude was modulated both by reward condition and by variation in target detectability inherent to our task. We further quantified this exogenous influence, showing that P3 differences reflected single-trial variation in P3 amplitude for different targets. These findings provide theoretical insight into the neural indices of reward in an RSVP task, and have important applications in the field of satellite imagery analysis.